2020
DOI: 10.2147/cia.s263216
|View full text |Cite
|
Sign up to set email alerts
|

<p>Incidence, Predictors, and Strategies for Failure of Retrograde Microcatheter Tracking After Successful Wiring of Septal Collateral Channels in Chronic Total Occlusions</p>

Abstract: Background: Retrograde microcatheter collateral channel (CC) tracking after successful wiring of septal CC is crucial for retrograde revascularization of coronary chronic total occlusion (CTO). However, the incidence, predictors, and strategies for failure of retrograde microcatheter CC tracking after successful wiring of septal CC remain unclear. Methods: In total, 298 patients with CTO who underwent retrograde septal CC PCI between January 2015 and May 2019 were retrospectively analyzed. Clinical data were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…In our study, dedicated microcatheters such as Corsair Pro, Corsair Pro XS, Caravel, Turnpike LP and Mamba Flex were used for initial microcatheter tracking compared to the Zhong et al in which Finecross was the initial microcatheter in most cases of switching (Supporting Information: Table ). Moreover, in one study, the use of the Finecross was an independent predictor of MTF during retrograde CTO PCI 14 . Recently, Ioppolo et al 15 have investigated angiographic predictors of septal tracking and found that small size and length of collaterals were an independent predictors of MTF.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In our study, dedicated microcatheters such as Corsair Pro, Corsair Pro XS, Caravel, Turnpike LP and Mamba Flex were used for initial microcatheter tracking compared to the Zhong et al in which Finecross was the initial microcatheter in most cases of switching (Supporting Information: Table ). Moreover, in one study, the use of the Finecross was an independent predictor of MTF during retrograde CTO PCI 14 . Recently, Ioppolo et al 15 have investigated angiographic predictors of septal tracking and found that small size and length of collaterals were an independent predictors of MTF.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, in one study, the use of the Finecross was an independent predictor of MTF during retrograde CTO PCI. 14 Recently, Ioppolo et al 15 have investigated angiographic predictors of septal tracking and found that small size and length of collaterals were an independent predictors of MTF. At the same time, small size, tortuosity, and exit angle <90°were predictors for guidewire tracking failure, proposing the new R-ICPS score ("retrograde-interventional collateral predictor score") to predict CC crossing.…”
Section: Discussionmentioning
confidence: 99%
“…A study that included 371 consecutive retrograde CTO‐PCI procedures between March 2015 and January 2018 revealed that CCs entry, and exit angle of <90° were independently related to initial microcatheter CCs tracking failure for septal CCs [27]. And another study retrospectively analyzed 298 patients with CTO who underwent retrograde septal CCs PCI between January 2015 and May 2019 also demonstrated that CCs entry, and exit angle of <90° were variables independently associated with initial microcatheter CCs tracking failure in patients with CTO undergoing retrograde septal PCI [28]. Another controversial issue was whether retrograde CTO‐PCI should be the initial or secondary strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Then, a study by Wang et al. [25] suggested that the success rate of retrograde guidewires tracking via poor septal CCs (Werner's CC0–1) was high, with a relatively high procedural success rate. They revealed that a CC diameter <1 mm, well‐developed non‐septal collateral, and LAD‐CTO were independent predictors of guidewire tracking failure in patients undergoing retrograde CTO‐PCI via poor septal CCs.…”
Section: Discussionmentioning
confidence: 99%
“…A multiple guidewire technique and balloon anchoring technique are other options for stronger support. A corsair microcatheter with a micro-expansion function is preferable to improve the success rate of the intervention ( 20 ). High-pressure balloon inflations are typically used for BUs.…”
Section: Discussionmentioning
confidence: 99%